ST2 and IL-33 in pregnancy and pre-eclampsia - Granne, I; Southcombe, J; Snider, J; Tannetta, D; Child, T; Redman, C; Sargent, I (Public Library of Science, 2011)
Normal pregnancy is associated with a mild systemic inflammatory response and an immune bias towards type 2 cytokine production, whereas pre-eclampsia is characterized by a more intense inflammatory response, associated with endothelial dysfunction and a type 1 cytokine dominance. Interleukin (IL)-33 is a newly described member of the IL-1 family, which binds its receptor ST2L to induce type 2 cytokines. A soluble variant of ST2 (sST2) acts as a decoy receptor to regulate the activity of IL-33. In this study circulating IL-33 and sST2 were measured in each trimester of normal pregnancy and in women with pre-eclampsia. While IL-33 did not change throughout normal pregnancy, or between non-pregnant, normal pregnancy or pre-eclamptic women, sST2 was significantly altered. sST2 was increased in the third trimester of normal pregnancy (p<0.001) and was further increased in pre-eclampsia (p<0.001). This increase was seen prior to the onset of disease (p<0.01). Pre-eclampsia is a disease caused by placental derived factors, and we show that IL-33 and ST2 can be detected in lysates from both normal and pre-eclampsia placentas. ST2, but not IL-33, was identified on the syncytiotrophoblast layer, whereas IL-33 was expressed on perivascular tissue. In an in vitro placental perfusion model, sST2 was secreted by the placenta into the 'maternal' eluate, and placental explants treated with pro-inflammatory cytokines or subjected to hypoxia/reperfusion injury release more sST2, suggesting the origin of at least some of the increased amounts of circulating sST2 in pre-eclamptic women is the placenta. These results suggest that sST2 may play a significant role in pregnancies complicated by pre-eclampsia and increased sST2 could contribute to the type 1 bias seen in this disorder.